Indian media : global approaches - Athique, Adrian (Cambridge, UK : Polity Press, 2012)
'The very rapid growth in the Indian media industries and the vibrancy of India's popular culture are making a working understanding of the Indian scene a prerequisite for any serious study of media in the twenty-first century. As one of the largest and most influential emerging economies in the world today, India now plays a crucial role in any serious discussion of social and economic change taking place at the global level. As new commercial and political alignments take shape in the face of new global circumstances, thinkers and decision-makers are inexorably drawn towards the reality of a new India being forged in the technological and cultural flux of global media flows. Taking an innovative interdisciplinary approach to the complex field of Indian media and society, this book combines a rich descriptive account with critical analysis designed to engender informed debate amongst students, academics and other researchers.'--P. [4] of cover.
Introduction: A Global Approach to the Indian Media -- Mass Media and the Making of Modern India -- Media Development and Mixed Messages -- Liberalization, Diversity and the Age of Television -- The Global Dynamics of Indian Media Piracy -- Digital India: Software, Services and Cybercultures -- Bollywood, Brand India and Soft Power -- Media Provision and the New Leisure Economy -- Afterword: Indian Media and the Asian Century.
Includes bibliographical references (p. 161-182) and index.
Keywords: Mass media -- India; Mass media -- Social aspects -- India